HUBUNGAN PROGRAM PROLANIS DENGAN PENGENDALIAN PENYAKIT HIPERTENSI DI WILAYAH KERJA PUSKESMAS BETOAMBARI KOTA BAU BAU - Nima Meilani; Eky Endriana Amiruddin; Fitriani Fitriani; Nurhudayah Nurhudayah; Kasmiati Kasmiati (Universitas Islam Negeri Alauddin Makassar, 2021)
Data from Puskesmas Betoambari show hypertension is often in the top 10 highest diseases in the puskesmas with increasing in cases in the last 3 years. In 2016 the number of cases was 109 cases, in 2017 was 580 cases and in 2018 was 580 cases. The purpose of this study is to know the relationship between Prolanis program, gymnastics, and hypertension controliing in the working area of Puskesmas Betoambari Baubau City. This is analytical observational with cross sectional study design. The population of this study is all participants Prolanis with hypertension in the puskesmas numbered 40 people. This study find that there is a relationship between the Prolanis and hypertension controlling in the working area of Puskesmas Betoambari. Puskesmas officers need to maximalize prolanis activities in order to motivate the community to follow every activity carried out to lower blood pressure.